Clutch size of Caiman latirostris (Crocodylia: Alligatoridae) varies on a latitudinal gradient - Simoncini, Melina Soledad (2009)
The distribution of the Broad-Snouted Caiman (Caiman latirostris) ranges from 5°S to 32°S. Thus, caiman populations are exposed to different climatic conditions, and this latitudinal gradient could affect aspects of their reproduction. In this study we present evidence that there is a positive relationship between clutch size and latitude. A possible effect of smaller clutch size  on populations from low latitudes could be increased nesting frequency, thus improving female fitness.